Investigation of microalgae gasification under steam atmosphere in downdraft gasifier by using aspen plus® - ÖZVEREN, UĞUR (My University, 2022)
Energy production faces environmental and economic problems due to growing population and fossil fuel uncertainty. These concerns have led researchers to find a widely available and renewable alternative such as biomass instead of fossil fuels. Microalgae is one of the most promising biofuels because it grows quickly and has a higher calorific value. Steam gasification is an alternative method to convert biomass into syngas with higher H2 content and lower CO2 content compared to other thermochemical conversion processes. In the present work, the downdraft gasifier model was developed using Aspen Plus® simulation software, which is capable of investigating the performance of microalgae gasification. Prior to the gasification performance evaluation, the validity of the model was tested with the results of an experimental study conducted with a different feedstock. The validation of the model was successfully completed, and it was found that the initial gas compositions of H2, CO2, CO and CH4 were very similar between the experimental study and the developed model. The effects of the main process parameters, such as the steam/biomass ratio and the gasification temperature, on the syngas composition and the higher heating value (HHV) of the syngas were evaluated. The results obtained with Aspen Plus® showed that increasing the temperature had a great effect on the H2 and CO composition of the syngas. They increased from 50.72% to 56.47% and from 28.11% to 28.84%, respectively. The simulation results also showed that the increasing S/B ratio favored the steam-related reactions and increased the H2 content in the syngas. However, a decreasing trend in CH4 content also decreased the HHV of the syngas as a function of temperature and steam. Keywords: Gasification; Biomass; Microalgae; Downdraft Gasifier; Aspen Plus®
Keywords: Gasification; Biomass; Microalgae; Downdraft Gasifier; Aspen Plus®